2020
DOI: 10.4315/jfp-20-115
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Liposome-Encapsulated Citral and Its Effect on the Shelf Life of Shatangju Mandarin

Abstract: Liposome-encapsulated citral was prepared by means of a hot homogenization method. The microstructure, particle size, and zeta potential of the capsules were analyzed by transmission electron microscope and dynamic light scattering, respectively, in which the results showed a good dispersion stability of the citral-loaded liposome. In vitro tests showed that liposome-encapsulated citral significantly (P < 0.05) reduced the populations of Escherichia coli, Bacillus subtilis, Staphylococcus aureus, and Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Rhizopus stolonifer growth is illustrated in Figure 7C, and it evidences an incapacity to thrive at concentrations of 3% or higher. The experimental results agreed with the results of a citral liposome inhibition by Chen et al [50]. Citral can inhibit the growth of microorganisms well.…”
Section: Fungal Growthsupporting
confidence: 89%
“…Rhizopus stolonifer growth is illustrated in Figure 7C, and it evidences an incapacity to thrive at concentrations of 3% or higher. The experimental results agreed with the results of a citral liposome inhibition by Chen et al [50]. Citral can inhibit the growth of microorganisms well.…”
Section: Fungal Growthsupporting
confidence: 89%
“…Vitamin C is extremely unstable, easily soluble in water and easily to be oxidized. It is a very important nutritional component of 'Shatangju' mandarins [Chen et al, 2020]. The changes of ascorbic acid content in 'Shatangju' mandarins can reflect the nutritional status during the postharvest storage.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, how to delay the deterioration of the fruit quality and flavor during transportation and storage, inhibit the occurrence of various postharvest diseases, and prolong the storage time are urgent problems to be solved. The main storage and preservation techniques for 'Shatangju' mandarin in China is the use of chemical preservatives, such as pyrimethanil, prochloraz, and iminoctadine triacetate [Chen et al, 2020]. Long-term use of these chemical preservatives will cause microbial resistance on the surface of fruits, leading to their reduced efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the antimicrobial activity of citral against C. albicans and some bacteria (E. coli and B. cereus) was enhanced when it was encapsulated in nanostructured lipid carriers (74.8 nm), as citral encapsulates showed lower MIC values than those of the citral emulsion for all microorganisms evaluated [128]. Additionally, Chen et al [129] reported that liposome-citral nanoencapsulates (105.7-238.0 nm) significantly improved the quality of fresh Shatangju mandarins compared to free citral-treated samples by reducing their weight loss and microbial spoilage after storage at 25 • C and 60-70% relative humidity (RH) for 26 d. Nanoemulsions containing citral have also shown outstanding effects when incorporated into coatings as vehicles, such as the case of the study reported by Machado [130], where alginate-based coatings that include citral nanoemulsions, in an optimal concentration between 0.1-0.5%, were a good barrier against microbial attack, while the quality parameters of the fruit were positively affected (e.g., color and respiration rate) during storage for 12 d at 4 • C and 90% RH. Cabbage and chicken skin 0.03 and 0.06% of citral Antimicrobial activity against L. monocytogenes and S. aureus in cabbage.…”
Section: Use As a Possible Food Additivementioning
confidence: 97%